(untitled) (Research, Society and Development, 2021)
The family Vochysiaceae, representative for Brazilian Cerrado, does not stand out in Caatinga environments. Due to the lack of studies that address the behavior of species of this family in disjunct Cerrado environments, this study aimed to investigate structural, ecological and phenological aspects of Qualea parviflora and Callisthene fasciculata populations. The phytosociological and phenological surveys were carried out in a Cerrado enclave at Serra do Boqueirão, Lavras da Mangabeira municipality, Southern Ceará, Brazil. Twelve sampling units of 12.0 x 30 m (0.432 ha) were plotted randomly, including all living individuals with a ground level diameter ≥ 3 cm, also measuring total heights. For the evaluation of phenophases, the Fournier percentage was used, allowing the estimation of intensity of the phenophase in each individual through a semi-quantitative interval scale of five categories (0 to 4), 0 being equivalent to 0%; (1) 1 to 25%; (2) 26 to 50%; (3) 51 to 75% and (4) 76 to 100%. Each sample was composed of 103 and 78 individuals respectively in 66.6% and 91.6% of the plots, of Q. parviflora and C. fasciculata, respectively. The spatial distribution, measured by the Dispersion (ID) and Morisita (IM) indexes reached the values of 17.14 and 18.26 (ID) and 1.08 and 1.16 (IM), respectively, indicating that the species have an aggregate distribution. The phenophases generally correlated with all the climatic variables studied in the region such as rain and preciptation. All data and results presented here collaborate for future projects in the area.